HYDRODYNAMIC CALCULATION OF THRUST BEARING WITH FLEXIBLE MOUNTING FACE OPERATING ON MICROPOLAR GREASING - Kamil S. Akhverdiyev; Inna S. Semenko (Advanced Engineering Research)
The computation method of the thrust plain bearing with flexible mounting face based on the equations of micropolar fluid motion and Lame's equations for a 'thin-layer' case is offered.  The impact assessment of dimensionless criteria values characteristic of the micropolar fluid, and the elastohydrodynamic parameter on the basic operation factors of the bearing is given.